The Correlation Between Pregnant Women Knowledge About Covid-19 and Its Transmission Prevention Behavior During Pregnancy - Rezma Latifah Hanum; Farida Fitriana (Placentum, 2023)
Background: Coronavirus Disease (COVID-19) is an infectious disease that can be transmitted from human to human through coughing/sneezing droplets (droplets). Pregnant women are a group that is vulnerable to the risk of being infected with COVID-19, furthermore it is necessary to take some preventive actions toward COVID-19. According to the literature review and previous research, knowledge is one of the factors that influence health behavior.